2013
DOI: 10.1208/s12248-013-9471-9
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Rapid Genotyping of SLCO1B1 388A>G and 521T>C in Human Blood Specimens Using the SmartAmp-2 Method

Abstract: Abstract. Organic anion-transporting polypeptide (OATP) 1B1, encoded by the solute carrier organic anion transporter family member 1B1 (SLCO1B1) gene, mediates the active uptake of various organic anions into hepatocytes and determines their hepatic clearances as the first step in the detoxification pathway. Previous reports indicated that alterations in its function by drug-drug interactions or genetic polymorphisms affect the pharmacokinetics of the substrate drugs. In the present study, we developed a metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Yoshida et al reported quaternary ammonium salt muscle relaxants transited from blood to liver cells mainly through the organic anion transporters. Organic anion‐transporting polypeptide (OATP) 1B1, which is encoded by the solute carrier organic anion transporter family member 1B1 (SLCO1B1) gene, mediates the active uptake of various organic anions into hepatocytes and determines their hepatic clearance as the first step in the detoxification pathway . Previous reports indicated that alterations in function by drug‐drug interactions or genetic polymorphisms affected the pharmacokinetics of the drugs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yoshida et al reported quaternary ammonium salt muscle relaxants transited from blood to liver cells mainly through the organic anion transporters. Organic anion‐transporting polypeptide (OATP) 1B1, which is encoded by the solute carrier organic anion transporter family member 1B1 (SLCO1B1) gene, mediates the active uptake of various organic anions into hepatocytes and determines their hepatic clearance as the first step in the detoxification pathway . Previous reports indicated that alterations in function by drug‐drug interactions or genetic polymorphisms affected the pharmacokinetics of the drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Rocuronium belongs to single quaternary ammonium muscle relaxant. Yoshida et al reported 1,19 quaternary ammonium salt muscle relaxants transited from blood to liver cells mainly through the organic anion transporters. OATP 1B1, which is encoded by the solute carrier organic anion transporter family member 1B1 (SLCO1B1) gene, mediates the active uptake of various organic anions into hepatocytes and determines their hepatic clearances as the first step in the detoxification pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SLCO1B1 codes for a transport protein essential for the entry of statins to the hepatocytes. The variant c.521T > C produces a loss of activity of the protein and it is known to be related to the development of secondary effects of statin treatment . CYP3A4 codes for an isoform of P450 cytochrome, and it is involved in the initial metabolism of statins, reducing their bioavailability.…”
Section: Introductionmentioning
confidence: 99%
“…The variant c.521T > C produces a loss of activity of the protein and it is known to be related to the development of secondary effects of statin treatment. [15][16][17] codes for an isoform of P450 cytochrome, and it is involved in the initial metabolism of statins, reducing their bioavailability. The variant (c.-392G > A) inhibits the binding of a repressor to the promoter, so there is an over-expression of the protein and a greater degradation of the drug.…”
mentioning
confidence: 99%